Regulatory T Cells in Respiratory Health and Diseases - Singh, Rani; Alape, Daniel; de Lima, Andrés; Ascanio, Juan; Majid, Adnan; Gangadharan, Sidhu P. (Pulmonary Medicine, 2019)
Respiratory diseases compromise the health of millions of people all over the world and are strongly linked to the immune dysfunction. CD4+FOXP3+ T regulatory cells, also known as Tregs, have a central role maintaining tissue homeostasis during immune responses. Their activity and clinical impact have been widely studied in different clinical conditions including autoimmune diseases, inflammatory conditions, and cancer, amongst others. Tregs express transcription factor forkhead box P3 (FOXP3), which allows regulation of the immune response through anti-inflammatory cytokines such as IL-10 or transforming growth factor beta (TGF-β) and direct cell-to-cell interaction. Maintenance of immune tolerance is achieved via modulation of effector CD4+ T helper 1, 2 or 17 (Th1, Th2, Th17) cells by Tregs. This review highlights the recent progress in the understanding of Tregs in different disorders of the respiratory system.